1982
DOI: 10.1071/bi9820223
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Induction of Parturition in Ewes with Dexamethasone or Oestrogen on Concentrations of Immunoglobulins in Colostrum, and Absorption of Immunoglobulins by Lambs

Abstract: Immunoglobulins were measured in colostral whey from untreated ewes or ewes treated on days 142-145 of gestation with 15 mg oestradiol benzoate (ODB) or 10, 17·5 or 25 mg dexamethasone m-sulfobenzoate (DEX) to induce parturition. DEX at all levels reduced the concentrations of immunoglobulins in colostrum, but ODB had no effect. In a second experiment, similar treatments of ODB and DEX were applied on day 143 of gestation. Lambs were removed from their dams at birth and fed a standard volume of pooled colostru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
7
1
Order By: Relevance
“…Comparison of the colostral IgG levels among the groups showed significant differences between GR II and GR III at 48 hours, which was not clinically important. In contrast to the results of the present study, some researchers (11,15) have determined that IP reduces the colostral IgG levels. At parturition, the colostral IgG level was highest in GR IV, but the increase was not significant.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Comparison of the colostral IgG levels among the groups showed significant differences between GR II and GR III at 48 hours, which was not clinically important. In contrast to the results of the present study, some researchers (11,15) have determined that IP reduces the colostral IgG levels. At parturition, the colostral IgG level was highest in GR IV, but the increase was not significant.…”
Section: Discussioncontrasting
confidence: 99%
“…Hormonal alterations following IP may negatively affect the colostral IgG level (10,11,23). IP with 10, 17.5 and 25 mg doses of dexamethasone at the 142nd-145th days of gestation causes a decrease in the colostral IgG levels in ewes (15). In goats, IP with a PGF 2α analog resulted in higher colostral IgG levels in the control group than in the induced group, because prolactin reached its peak level 24 hours before parturition, stimulated lactogenesis and terminated the transfer of IgG to mammary secretions (11).…”
Section: Discussionmentioning
confidence: 99%
“…hormones (Dawe, Husband, & Langford, 1982;Green, Hunter, & Mann, 2005). The oestrogen receptor (ER), androgen receptor (AR) and progesterone nuclear receptor (PGR) are all members of the nuclear receptor family (Patel et al, 2015;Tsai & O'Malley, 1994).…”
mentioning
confidence: 99%
“…In addition to endogenous hormones, exogenous hormones can also affect colostrum yield and composition (Dawe et al, 1982;Field et al, 1989). It has been reported that sows chemically induced to farrow trended toward the production of less colostrum and that the colostrum contained less fat (Farmer and Quesnel, 2009;Jackson et al, 1995;Milon et al, 1983).…”
Section: Discussionmentioning
confidence: 99%